Transportation, a key sector for the networking of intermediate cities Case of the wilaya of Tizi-Ouzou Le transport, un secteur clé pour le maillage en réseau des villes intermédiaires Cas de la wilaya de Tizi-Ouzou - ايت طالب, عبد الحميد (جامعة مسيلة, 2018)
Recent urban mutations are causing profound disruption in the perception, use and organization of space. In all Algerian wilayas, urban concentration is mostly concentrated in large cities, leaving little place for other smaller cities and thus giving rise to a spatial and functional imbalance of the territory. This is the case of the wilaya of Tizi-Ouzou. With 80% of rural areas, the urban network of the wilaya of Tizi-Ouzou is identified to the agglomeration of Tizi-Ouzou where all urban functions are concentrated, which explains the importance of the flows entering this agglomeration thus generating a congestion of the places. Therefore, in this work, we will focus on intermediate cities and the need to appreciate the importance of their role in reducing disparities and imbalances, through their specificity in terms of spatial organization, through their role as a link and intermediary between urban and rural areas. For a better structuration and territorial cohesion, we were interested to intermediate cities and to the need of appreciating the importance of their role in reducing disparities and imbalances through their specificity in terms of spatial organization by their role as links and intermediaries between urban and rural areas. In order to these cities fulfil this mission, in particular the opening up of rural areas and the decongestion of large urban centres, they must have an efficient and effective transport system capable of ensuring attractiveness and connectivity. The attractiveness of a city depends on its accessibility and the level of its transport infrastructure provision, but also on its degree of connection to networks and communication way. In other words, more a city is armed with an efficient transport system, more it attract people and investment. So, transport is more than ever a key sector for the socio-economic development of any territory but also for overcoming spatial discontinuity. Through this paper, we will try to demonstrate that with a structured transport system, the intermediate cities of the wilaya of Tizi-Ouzou would succeed in reducing territorial inequalities between urban centres and rural areas.
Keywords: : intermediate cities; transportation system; socio-economic development. Jel Classification Codes: O18, R4, R11.